If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(8x + -4) = 10x + -9 Reorder the terms: 0.5(-4 + 8x) = 10x + -9 (-4 * 0.5 + 8x * 0.5) = 10x + -9 (-2 + 4x) = 10x + -9 Reorder the terms: -2 + 4x = -9 + 10x Solving -2 + 4x = -9 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -2 + 4x + -10x = -9 + 10x + -10x Combine like terms: 4x + -10x = -6x -2 + -6x = -9 + 10x + -10x Combine like terms: 10x + -10x = 0 -2 + -6x = -9 + 0 -2 + -6x = -9 Add '2' to each side of the equation. -2 + 2 + -6x = -9 + 2 Combine like terms: -2 + 2 = 0 0 + -6x = -9 + 2 -6x = -9 + 2 Combine like terms: -9 + 2 = -7 -6x = -7 Divide each side by '-6'. x = 1.166666667 Simplifying x = 1.166666667
| -3x-152+40x=20 | | 12=.99x+20.76 | | 3(x+17.50)=136.50 | | 0=(x^3)-(x^2)-20 | | X+2=16-28 | | 8(x-1)-2(3x-1)=x-1 | | -5t+5=-5 | | 2-2(5y+7)=2(-6-2)+1 | | 5(g+12)=145 | | 0=x^3-7x^2-9x+63 | | -3c+2=7 | | 20+2x=4x-68 | | 0.1x+x=93 | | 8x-7=3z-7z+5 | | 8x+4-36x+9=3 | | 4i=2 | | 4x^2-25y^2+8x+50y-121=0 | | 4x^2-43+63=0 | | a+c=1 | | 0=x^2+3x+9 | | 8*(x+2)=4*(x+5) | | 9x-6=11-2(X-8) | | -(1+8x)=35+4x | | 2+k=8 | | 1.5(2x+1)=x-7 | | Y=16-4x^2 | | -5(3+2r)=-3-6r | | 2m+4-8=18 | | 12x^2-10x+13=0 | | 32x=80 | | -5(3+2r)=-36r | | 3(k-8)=k+9 |